Hippocampal neurobiology and function in an aged mouse model of TDP-43 proteinopathy in an APP/PSEN1 background. (27th July 2021) - Arezoumandan, Sanaz; Cai, Xuezhu; Kalkarni, Praveen; Davis, Stephani A.; Wilson, Katherine; Ferris, Craig F.; Cairns, Nigel J.; Gitcho, Michael A.
Highlights: Survival reduced in mice expressing human TDP-43 in an APP/PSEN1 background. Significant neuronal loss and plaques reduced in TDP-43/APP/PSEN1 expressing mice. TDP-43/APP/PSEN1 mice show loss of functional coupling in hippocampus and amygdala. End of life study reveals some tumors evident regardless of genotype. Abstract: Aging is a major risk factor for Alzheimer's disease (AD), the most common cause of dementia worldwide. TDP-43 proteinopathy is reported to be associated with AD pathology is almost 50% of cases. Our exploratory study examined near end-stage (28 months old) mice selectively driving expression of human TDP-43 in the hippocampus and cortex in an APP/PSEN1 background. We hypothesized that hippocampal neuropathology caused by β-amyloidosis with TDP-43 proteinopathy induced in this model, resembling the pathology seen in AD cases, manifest with changes in resting state functional connectivity. In vivo magnetic resonance imaging and post-mortem histology were performed on four genotypes: wild type, APP/PSEN1, Camk2a/TDP-43, and Camk2a/TDP-43/APP/PSEN1. Our results revealed loss of functional coupling in hippocampus and amygdala that was associated with severe neuronal loss in dentate gyrus of Camk2a/TDP-43/APP/PSEN1 mice compared to APP/PSEN1 and wild type mice. The loss of cells was accompanied by high background of β-amyloid plaques with sparse phosphorylated TDP-43 pathology. The survival rate was also reduced in Camk2a/TDP-43/APP/PSEN1 mice compared to other groups. This end-of-life study provides exploratory data to reach a better understanding of the role of TDP-43 hippocampal neuropathology in diseases with co-pathologies of TDP-43 proteinopathy and β-amyloidosis such as AD and limbic predominant age-related TDP-43 encephalopathy (LATE).